Comparative study of diabetes foot diagnosis using ABPI - Hari Krishnan, G; S Arun Kumar, G; Arun, V; Saravana, R (International Journal of Engineering and Technology, 2018)
User friendly product has been developed to analyze the user condition accurately and provide a digital output with low cost product to the end user for diagnosing diabetes foot. Detecting the level of peripheral neuropathy which significantly increases the risk of sustaining a foot wound called â€˜loss of protective sensation. To implement a device to detect foot diabetes in patients using the Ankle Brachial pressure index values. The proposed system was tested by conducting experiment on 9 patients and whose ABPI value measured confirms the convention-al measured values.Â Â